Alessandro Luigini, Adnexūs. Una indagine interdisciplinare tra immagine disegno e arte, Libria editrice, Melfi (Potenza) 2020 (diségno, 2021)
Alessandro Luigini’s book, in its 12x16.5 cm format, presents itself as a small precious text capable of bringing together the multitude of theories that feed the debates on visual culture, tracing useful connections for the framing of ontologies and epistemologies that orbit outside and inside the image, drawing and their becoming ‘art’. [read more]   Alessandro Luigini’s book, in its 12 x 16.5 cm format, presents itself as a small precious text capable of bringing together the multitude of theories that feed the debates on visual culture, tracing useful connections for the framing of ontologies and epistemologies that orbit outside and inside the image, drawing and their becoming “art”.But what promises to be an interdisciplinary investigation, anticipated by the same monograph title, in fact articulates its own dialogical palimpsest in reflections expressed in terms of a transdisciplinary dissertation, as can also be deduce by reading the conclusions.As for the introductions, the connective pretexts, the adnexūs, here originate in the affective ties brought to light by the oculocentric sensorium linked to a memory that cannot help immortalizing the semblance of an embodied memory, so as to make its probable abandonment acceptable; therefore, the urgent need to hold it back fixes the image and stores it starting from the story of the Corinthian potter Butade daughter – handed down by Herodotus and recounted by Pliny the Elder in the first century BC –, whose torment for the sudden departure of her beloved drives her to trace the outline of his face, from the shadow outline projected on a wall.This legend, which became a very popular literary subject during the Enlightenment period, has been iconographical translated on several occasions into the drawing and painting origins, titling the works of famous artists such as Bartolomé Esteban Murillo, David Allan and Karl Friedrich Schinkel.The book starts right here: «From an image, a woman traces a drawing, and the art of clay portraits comes to life» [p. 8]. Thus, from the mythological origins of practices interconnected with the seeing act, we set off on a diachronic journey to investigate the role that the graphic sciences have played and continue to play in training courses at various levels. However, the intention is certainly not to provide a didactic methodology, but rather to problematise constantly evolving disciplinary fields, which are confronted with research whose positioning is located into the hybrid territories of visual culture.The first chapter focuses on the “image” definition, monitoring its restless transition from the hegemonies of anthropic materiality to the fiction domains, to extrapolate its genealogies from institutional knowledges and understand its common traits and disparities.It is the well-established philosophical debates that open the discourse, calling into question the Platonic deception of a mimesis inevitably imposed by the figuration of reproduced reality, where the act of translating it does not necessarily imply the choice of imitating it, but rather the need to interpret it. Thus, the reference to the cave allegory, described in the Republic of 360 BC, becomes the pretext for a Socratic exclusion of the artistic operation, whose semblance of truth is only evoked by the spectres of a shadow that cannot be looked. Aristotelian opposition, on the other hand, interweaves intellectual thought with the images that translate it and make it so.According to this perspective, thought does not exist without images, because this conviction «undermines to the foundations of the claim to be able to do without, whether in logical, mathematical or philosophical awareness, the lowering of lines, colours and volumes in order to rise, finally freed, to the rarefied sky of pure incorporeal concepts» [Pinotti, Somaini 2014, p. 12].Within this game of rhetorical positionings, Alessandro Luigini establishes a dialectic of being, becoming and codify the image, in which the conscious decision to reduce the iconographic apparatus to a minimum is explained by the need to resort to representation only and exclusively when one wishes to emphasise the underlying assumptions that substantiate itself.Thus, Leonardo da Vinci’s painting of the Lady with an Ermine is tripartite, following the precepts of Husserl’s phenomenology, in order to codify the perceptive qualities of the iconic thing, the object and the iconic subject. On the other hand, the pervasive production of images transmitted by digital devices is explored in its constructive processes, starting with the first manifestations and the work of artists exploring the concept of pixels, as for example we can find in the Chuck Close works.The second chapter is dedicated to the origins and evolution of drawing, articulated in its double meaning of expressive language and design practice which, as a subjective act, opens to co-creation when the paradigm shift is supported by the information technology devices in use. Then the focus shifts to perceptual aspects and returns to individuality, demonstrating that drawing is not as the result of an invention as the result of a distant discovery.According to the psychologist John Kennedy studies, the ability to recognise the graphic signs of silhouettes by indigenous peoples less accustomed to the production of visual artefacts is superior to the degree of reading of those who have already experienced and produced the same figural representations. Thus, the reference to the print and profile of the shadow, on which the book’s preconditions are structured, echoes the meanings that accompany the first steps of the child's imaginative transposition through scribbling.So much so that the author emphasises how «the level of drawing conceptualisation and abstraction requires greater intellectual stimulation as the level of iconicity decreases – that is, as it progressively moves away from mimetic similarity with reality – while in the development of the child's sign – realism – is a goal that is pursued with successive cultural refinements of a natural instinct» [pp. 79-80].The graphic and visual sciences pedagogical models are debated according to an inclusive approach that sees the two disciplines contributing for a taxonomic classification, completely open and non-hierarchical, within which to converge new terminologies of an expanded drawing grammar.In keeping with the title, the last chapter seems to be devoted to artistic practices in general, but the term art stigmatises the current pluralisms that draw a distinction between visual and performing arts, although the discussion should focus exclusively on the firsts.Thus, the theoretical apparatus that sentences the ontological presuppositions immediately distances itself from Crocian thought linked to the imagination and autonomy of art, in order to emphasise the value of belonging to the cultures that practice and enjoy it.The return to the origins of the term is intertwined with the declinations of the beauty concept, which assumes its founding role in the debates of aesthetics: a discipline that achieves its autonomy as a science of sensitive knowledge according to Baumgarten theory. But the dense examination continues, arriving at our contemporary times, intercepting the work of Edgar Morin, according to whom it is precisely art that generates aesthetic emotion.The paragraph that closes chapter three treats aesthetic education, in the primary educational trainings that focus on artistic practices, not so much as a mere imposition of beauty canons, but rather to stimulate sensitivity, imagination and the expressive act. For the author, these objectives can only «be achieved by involving the child in creative activities that provoke real participation and confront him with new problems that allow him to unblock one-way thinking and prefigure new solutions, ultimately generating real cognitive restructuring» [p. 115].The conclusions of this significant contribution offered by Alessandro Luigini, as well as outlining the trajectories of an expandable taxonomy for visual and graphic sciences, within which drawing assumes a central role, are also a stimulus to reflect on the fields of action and tools of the scientific disciplinary sector: ICAR/17. Hence the need to trace the concepts and key words, that animate the three chapters, back to the tree diagram of visual sciences proposed by Bertoline in 1998. AuthorMassimiliano Ciammaichella, Department of Architecture and Arts, Università Iuav di Venezia, massimiliano.ciammaichella@iuav.it Reference ListPinotti, A., Somaini, A. (edited by). (2014). Teorie dell’immagine. Il dibattito contemporaneo. Milano: Raffaello Cortina.